YouTube as an informational source for brachial plexus blocks: evaluation of content and educational value - Selvi,Onur (2019)
Abstract Background and objectives: YouTube, the most popular video-sharing website, contains a significant number of medical videos including brachial plexus nerve blocks. Despite the widespread use of this platform as a medical information source, there is no regulation for the quality or content of the videos. The goals of this study are to evaluate the content of material on YouTube relevant to performance of brachial plexus nerve blocks and its quality as a visual digital information source. Methods: The YouTube search was performed using keywords associated with brachial plexus nerve blocks and the final 86 videos out of 374 were included in the watch list. The assessors scored the videos separately according to the Questionnaires. Questionnaire-1 (Q1) was prepared according to the ASRA guidelines/Miller's Anesthesia as a reference text book, and Questionnaire-2 (Q2) was formulated using a modification of the criteria in Evaluation of Video Media Guidelines. Results: 72 ultrasound-guided and 14 nerve-stimulator guided block videos were evaluated. In Q1, for ultrasound-guided videos, the least scores were for Q1–5 (1.38) regarding the complications, and the greatest scores were for Q1–13 (3.30) regarding the sono-anatomic image. In videos with nerve stimulator, the lowest and the highest scores were given for Q1–7 (1.64) regarding the equipment and Q1–12 (3.60) regarding the explanation of muscle twitches respectively. In Q2, 65.3% of ultrasound-guided and 42.8% of blocks with nerve-stimulator had worse than satisfactory scores. Conclusion: The majority of the videos examined for this study lack the comprehensive approach necessary to safely guide someone seeking information about brachial plexus nerve blocks.